(untitled) (Majalah Kedokteran Bandung, 2023)
Over the last decade, the global prevalence of hypertension rate has increased by 5.2% and, in Indonesia, the prevalence rate has increased significantly from 25.8% in 2013 to 34.1% in 2018. Hypertension treatments using blood pressure-lowering drugs, such as angiotensin-converting enzyme (ACE) inhibitors, often cause unpleasant side effects. These side effects increase the interest in using potentially effective natural remedies, such as garlic. This study aimed to determine which organosulfur compounds in garlic can act as an ACE inhibitor to reduce blood pressure in hypertension using a cheminformatics approach. Eighteen organosulfur compounds of Allium sativum L. were screened based on Lipinski’s rules and ADMET evaluation. Seven compounds passed the screening and were subjected to QSAR analysis, molecular docking analysis, and molecular dynamics simulations to assess the stability of the protein. The seven compounds then underwent molecular docking and QSAR analysis. Ajoene (4,5,9-trithiadodeca-1,6,11-triene-9-oxide) and S-allylmercaptocysteine (SAMC) were two compounds with better docking values compared to the positive control compound. The QSAR analysis also showed that SAMC had an activity as an ACE inhibitor. The ADMET evaluation showed that Ajoene and SAMC had good absorption and could not penetrate the blood-brain barrier. Molecular dynamics simulation of ACE complexes Ajoene, SAMC, and Captopril ranged from 0.05 to 5.61 Ã… but exhibited a pattern of synonymous fluctuations for most residues. Based on the simulation data, the organosulfur compounds from garlic, Ajoene, and SAMC are proven to have a mechanism of action as ACE inhibitors to reduce blood pressure in hypertension.